Network Coded Noncoherent Cooperative Communications - Karabulut, Muhammet Ali; Ilhan, Haci; Ozdemir, Ozgur (IEEE, 2014)
In recent years, network coding has received significant attention as an innovative approach that improves the spectral efficiency of wireless communication systems. The Multiple Access Relay Channel (MARC) where multiple users communicate with a common destination via a relay, is one of the important network coding applications in wireless cooperative communications. In this paper, error performance of MARC system non-coherent BFSK technique is studied. This technique, which employs training sequences, is a prominent approach for decreasing the system complexity and cost by eliminating the need for channel estimation. The numerical results for Rayleigh fading channels have shown that proposed approach provides full diversity gain.
Keywords: multiple access relay channel; network coding; non-coherent BFSK; MODULATION; DIVERSITY; Engineering; Telecommunications